The Obesity Paradox in Sepsis: A Theoretical Framework. Issue 2 (April 2020) - Robinson, Jamie; Swift-Scanlan, Theresa; Salyer, Jeanne; Jones, Terry
Sepsis is a life-threatening syndrome that occurs in response to a severe infection. In recent years, the understanding of the pathobiology of sepsis has been refined, with research describing an altered host response as the underlying cause. Survivors of sepsis often have long hospital stays and suffer from subsequent frailty and long-term health consequences. Predicting attributes of sepsis survivors remains challenging; however, an obesity paradox exists, wherein obese individuals survive sepsis at higher rates than their normal-weight counterparts. We present a model that describes the relationships between sepsis and obesity, focusing on inflammation as a shared pathway for dysregulation in obese and healthy-weight adults. Understanding the interaction of these complex variables is an important first step toward developing interventions and treatments to augment sepsis survival.